Drymonia tomentulifera, sp. nova de Costa Rica, y notas sobre la biología reproductiva del género Drymonia (Gesneriaceae: Episcieae) - Kriebel, Ricardo (Lankesteriana: International Journal on Orchidology, 2015)
A new species of the neotropical genus Drymonia, D. tomentulifera, is described and illustrated, and compared to D. pilifera. Notes on the reproductive biology, especially the widespread occurrence of protandry in the genus Drymonia are included.